PEMBERDAYAAN ANGGOTA PKK DALAM PENGELOLAAN OBAT DAN BEYOND USE DATE (BUD) DI KELURAHAN KAUMAN KOTA MALANG - Sirilus Deodatus Sawu; Venny Kurnia Andika (Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
Storage of medicines is an important aspect in ensuring the effectiveness of the medicine when consumed. Some medicines need to be stored in a special place such as a refrigerator. The length of time medicines are stored generally follows the expiry date (ED), which is the time limit for use of the medicine after it is produced by the pharmaceutical factory before the primary packaging is opened. If the primary packaging has been opened, it follows the beyond use date (BUD). The public sometimes pays little attention to where a drug is stored and how long it is stored. The aim of the activity is to provide knowledge for PKK members in Kauman Village, Malang City about storing medicines, especially those that require special storage and Beyond Use Date (BUD) of medicines. The method used is providing information and knowledge regarding drug management in the household, especially regarding drug storage and Beyond Use Date (BUD) with a socialization method implemented 3 (three) times. The results of the socialization activities from the first to the third stages ran smoothly. From the evaluation results, it is known that the knowledge of the 20 PKK members of Kauman Village, Malang City, who were involved, experienced an increase, where from the pre-test the average score was 6.60, while the post-test results averaged a score of 8.15. The percentage increase in knowledge based on the average post-test score was 23.4%. For this reason, when providing drug services, we are expected to always provide education regarding storage and how long the drug can be stored.